2013
DOI: 10.1016/j.cub.2013.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Shocking Revelations and Saccharin Sweetness in the Study of Drosophila Olfactory Memory

Abstract: It is now almost forty years since the first description of learning in the fruit fly Drosophila melanogaster. Various incarnations of the classic mutagenesis approach envisaged in the early days have provided around one hundred learning defective mutant fly strains. Recent technological advances permit temporal control of neural function in the behaving fly. These approaches have radically changed experiments in the field and have provided a neural circuit perspective of memory formation, consolidation and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 139 publications
2
83
0
1
Order By: Relevance
“…We know that the Kenyon cells decode the combinatorial odor code-that is, they provide the tag associated with any odor-because flies have been shown to use the output of Kenyon cells to learn odors that have been paired with reward or punishment (26). The previous section demonstrated that odors are represented in a distributed way over the population of Kenyon cells, but to see how these cells provide a (close to) unique output for each odor, we need to know properties of the combinatorial code produced by the antennal lobe.…”
Section: A Distributed Representation Of Olfactory Information In Thementioning
confidence: 99%
“…We know that the Kenyon cells decode the combinatorial odor code-that is, they provide the tag associated with any odor-because flies have been shown to use the output of Kenyon cells to learn odors that have been paired with reward or punishment (26). The previous section demonstrated that odors are represented in a distributed way over the population of Kenyon cells, but to see how these cells provide a (close to) unique output for each odor, we need to know properties of the combinatorial code produced by the antennal lobe.…”
Section: A Distributed Representation Of Olfactory Information In Thementioning
confidence: 99%
“…The exposure of flies to repetitive training cycles with gaps between the training cycles (spaced training) leads to a consolidated form of long-term memory that is CREB transcription dependent and lasts up to a week. Training without gaps (massed training) leads to the formation of anesthesia-resistant memory (ARM), which similar to long-term memory, is typically measured 24 hr after 5 cycles of training 7,13,[15][16][17]20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…The promoter-driven expression of light-or temperature-sensitive transgenes to activate or block the neural activity of specific neurons allows one to investigate which neurons are required for memory acquisition, consolidation and retrieval 3,4,11,15,16,20,[22][23][24] . Memory at 1 hr is typically measured when studying age-related memory impairment because this form of memory appears particularly vulnerable to the effects of ageing [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations